Al-Islam Learning Development on Local Wisdom based: Efforts to Strengthen the Concept of Indonesian Students Religious Moderation - Andi Trisnowali; A. Fajar Awaluddin; Fajri Dwiyama; Muh. Alfian; Ilham Ilham; Dilham Dilham (International Journal of Asian Education, 2022)
Studies about the integration value of students’ religious moderation have been conducted by many scholars, in fact, there are still limited studies on the relationship between them in the aspect of local wisdom. To fill the gap, this study aims to describe the value of Buginess local wisdom called Mattulu Tellue which can be found in the religious moderation material in Al-Islam learning in the Muhammadiyah University Bone, Indonesia to improve tolerance among students. This study deploys a qualitative method. This study found that lecturers of Al-Islam learning apply the local wisdom in the planning, implementation, and evaluation of learning to strengthen the value of religious moderation education based on Bugis local wisdom in al-Islam learning. Al-Islam learning with the theme of religious moderation based on the values of Bugis Bone Mattulu Tellue local wisdom has positive impacts on students which can contribute to society, especially in areas that are still full of culture and local wisdom in understanding the value of tolerance in the moderation frame. religious. Therefore, this study gives implications to contribute empirically, contextually, and policy.